HSF1 facilitates the multistep process of lymphatic metastasis in bladder cancer via a novel PRMT5‐WDR5‐dependent transcriptional program. Issue 5 (18th April 2022) - Huang, Ming; Dong, Wen; Xie, Ruihui; Wu, Jilin; Su, Qiao; Li, Wuguo; Yao, Kai; Chen, Yuelong; Zhou, Qianghua; Zhang, Qiang; Li, Wenwen; Cheng, Liang; et al.
Abstract: Background: Lymphatic metastasis has been associated with poor prognosis in bladder cancer patients with limited therapeutic options. Emerging evidence shows that heat shock factor 1 (HSF1) drives diversified transcriptome to promote tumor growth and serves as a promising therapeutic target. However, the roles of HSF1 in lymphatic metastasis remain largely unknown. Herein, we aimed to illustrate the clinical roles and mechanisms of HSF1 in the lymphatic metastasis of bladder cancer and explore its therapeutic potential. Methods: We screened the most relevant gene to lymphatic metastasis among overexpressed heat shock factors (HSFs) and heat shock proteins (HSPs), and analyzed its clinical relevance in three cohorts. Functional in vitro and in vivo assays were performed in HSF1‐silenced and ‐regained models. We also used Co‐immunoprecipitation to identify the binding proteins of HSF1 and chromatin immunoprecipitation and dual‐luciferase reporter assays to investigate the transcriptional program directed by HSF1. The pharmacological inhibitor of HSF1, KRIBB11, was evaluated in popliteal lymph node metastasis models and patient‐derived xenograft models of bladder cancer. Results: HSF1 expression was positively associated with lymphatic metastasis status, tumor stage, advanced grade, and poor prognosis of bladder cancer. Importantly, HSF1 enhanced the epithelial‐mesenchymal transition (EMT) of cancer cells in primary tumor to initiate metastasis, proliferation of cancer cells in lymph nodes, and macrophages infiltration to facilitate multistep lymphatic metastasis. Mechanistically, HSF1 interacted with protein arginine methyltransferase 5 (PRMT5) and jointly induced the monomethylation of histone H3 at arginine 2 (H3R2me1) and symmetric dimethylation of histone H3 at arginine 2 (H3R2me2s). This recruited the WD repeat domain 5 (WDR5)/mixed‐lineage leukemia (MLL) complex to increase the trimethylation of histone H3 at lysine 4 (H3K4me3); resulting in upregulation of lymphoid enhancer‐binding factor 1 (LEF1), matrix metallopeptidase 9 (MMP9), C‐C motif chemokine ligand 20 (CCL20), and E2F transcription factor 2 (E2F2). Application of KRIBB11 significantly inhibited the lymphatic metastasis of bladder cancer with no significant toxicity. Conclusion: Our findings reveal a novel transcriptional program directed by the HSF1‐PRMT5‐WDR5 axis during the multistep process of lymphatic metastasis in bladder cancer. Targeting HSF1 could be a multipotent and promising therapeutic strategy for bladder cancer patients with lymphatic metastasis.